2007
DOI: 10.1093/carcin/bgm005
|View full text |Cite
|
Sign up to set email alerts
|

Xanthorrhizol inhibits 12-O-tetradecanoylphorbol-13-acetate-induced acute inflammation and two-stage mouse skin carcinogenesis by blocking the expression of ornithine decarboxylase, cyclooxygenase-2 and inducible nitric oxide synthase through mitogen-activated protein kinases and/or the nuclear factor- B

Abstract: Xanthorrhizol is an active component isolated from Curcuma xanthorrhiza Roxb. (Zingiberaceae) that is traditionally used in Indonesia for medicinal purposes. In the present study, we found that the topical application of xanthorrhizol before 12-O-tetradecanoylphorbol-13-acetate (TPA) treatment significantly inhibits TPA-induced mouse ear edema and TPA-induced tumor promotion in 7,12-dimethylbenz[a]anthracene (DMBA)-initiated ICR mouse skin. The topical application of xanthorrhizol following the induction of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 40 publications
5
84
1
1
Order By: Relevance
“…Because both c-Jun and JunB that play opposite roles in proliferation (41-43, 61) were increased in the KO mouse, overexpression of JunB could also counteract the proliferative effects of c-Jun. Furthermore, ERK and Akt have been identified as important regulators of NF-B activation in the skin (48,62,63), and consistent with this, we found that p65 phosphorylation was increased in the TR KO mice.…”
Section: Discussionsupporting
confidence: 88%
“…Because both c-Jun and JunB that play opposite roles in proliferation (41-43, 61) were increased in the KO mouse, overexpression of JunB could also counteract the proliferative effects of c-Jun. Furthermore, ERK and Akt have been identified as important regulators of NF-B activation in the skin (48,62,63), and consistent with this, we found that p65 phosphorylation was increased in the TR KO mice.…”
Section: Discussionsupporting
confidence: 88%
“…In our previous studies on carcinogenesis, xanthorrhizol suppressed cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) expression in lipopolysaccharide (LPS)-induced RAW 264.7 cells and exhibited antimetastasis activity in a mouse spontaneous lung metastasis model (9,10). Recently, we also reported cancer chemopreventive activity mediated by xanthorrhizol and a plausible mechanism of action in a mouse two-stage carcinogenesis model (11). However, the underlying mechanisms of action through which xanthorrhizol inhibits cancer cell growth are yet not fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory leukocytes, such as macrophages when activated by many stimuli, result in the induction of pro-inflammatory protein and enzymes including inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) [7]. Consequently, suppressing the induction of COX-2 and iNOS is a key strategy for cancer chemoprevention in various human organs [8].…”
Section: Introductionmentioning
confidence: 99%